Deskripsi Pelaksanaan Kesehatan Dan Keselamatan Kerja (K3) Di Perusahaan Panca Jaya - Wulan Ningsih; Agatha Ferijani (Universitas Katolik Soegijapranata, Semarang, 2019)
This research aimed to know how is the description of Occupational Health and Safety in Panca Jaya Company. The research subject was one as the owner of this noodle company. The primary data was about occupational health and safety of the company employees, taken by in depth interview. Based on data obtained, it was concluded that the program was conducted but still can be developed. The company provided medecines and first aid for accidents, work health and safety socialization. They also gave the employees BPJS and JAMSOSTEK (social security services), and the tool for fire extinguisher and first aid help (P3K). The company pro actively protect the employees but the first aid tools remained not in good condition and needed maintenance.